CAN IT BE A GENERIC?: A STUDY ON THE BUYING BEHAVIOR OF BRAZILIAN MEDICINE CONSUMERS - Froda, Isabela Alves (2020)
Main Goal: the objective of this study is to identify the factors that influence the consumer ithe purchase of medications and to understand the perception of consumers about the effectiveness of generics. Methodology: the study is characterized by a quantitative survey, in which 386 consumers of drugs participated, whose data were analyzed by means of descriptive statistics, bivariate correlation analysis and multiple linear regression. Originality: the study advanced in a gap regarding the identification of behavioral factors that may potentialize the acceptance of generic drugs in Brazil. Main results: we found that a large part of the sample does not recognize that a generic drug has the same effect as a reference drug. Theoretical contributions: we identified the factors that explain the perceived efficacy of generic drugs. Management contributions: promoting educational measures for the population and health professionals can be a good guideline, generating benefits by enabling the transfer of resources to investments in other areas of health.